Design and Development of Fish Natural Convection Drying Facility - Manuel A. Bajet, Jr (Philippine Association of Institutions for Research, Inc., 2013)
Fish drying facility was designed, developed and tested to determine itsperformance, and characterization as a natural convection dryer for stunted tilapia.Parameters in the study were air temperature, relative humidity, drying chamber,moisture content, drying time, capacity and rate. Experimental research design wasused and materials includes, lumber painted in black and used as frames, plasticscreen mesh, cellophane, black plain sheet and stones.. Findings disclosed that dryingrate were noted at the highest during first two hours internal with an average dryingrate of 7.20 grams per minute. Average drying rate after the three trials was 2.63grams per minute. The moisture content of the samples was reduced from 92.68%-75.23% during the 20 hours of drying and weights of fish samples were also reducedfrom 20 to 15 kilograms. Further, results on relative humidity was higher at theupper trays compared that the lower trays. Return of investment was 72% and has apayback period of 0.05 year. Â  Keywords: Renewable Energy, Project and Experimental Research, NaturalConvection Dryer, Vigan City, Ilocos Sur, Philippines